Quantification of methoprene aerosol deposition using reversed-phase high-performance liquid chromatography. (December 2022) - Norton, Amie E.; Brabec, Daniel L.; Tilley, Michael; Yeater, Kathleen M.; Scheff, Deanna S.
Abstract: Methoprene is an insect growth regulator (IGR), which acts on the juvenile stages of insects and is used as pest control method in food processing facilities. A chemical reference method was developed to quantitate aerosol deposition of methoprene using High-Performance Liquid Chromatography, HPLC. The method starts with placing 2.5 g (∼1 level tsp) flour in the opened Petri-dish (150 mm × 15 mm) as an absorber and placing the Petri dish on the floor and in the facility treated with pesticide aerosol. After treatment, the dishes were collected and analyzed with HPLC. The flour from each dish was emptied into a 50 mL centrifuge tube along with 40 mL of methanol and mixed. The samples were then centrifuged and loaded on the HPLC. The HPLC method could detect methoprene concentrations down to 0.2 μg/mL. In validation test, unknown samples matched the real spray times with a SE from 0.1 to 0.8. Historic methods used 120 min mixing time and 48 h holding time. It was found that a mixing time of 30 min and 0 holding time was sufficient to obtain greater than 90% recovery. The objective of this study was to develop a standard chemical methodology to quantify the amount of methoprene insecticide deposited on floors and surfaces when applied from compressed cylinders as an aerosol insecticide. The HPLC method developed explored the impact of flour, mixing, holding, and processing times on methoprene recovery. The HPLC method developed in this study will provide pesticide applicators a method to accurately determine product deposition and to evaluate pesticide distributions throughout facilities and determine areas which may require additional treatment. Highlights: A method was developed to collect samples of insecticide spray depositions using Petri dishes layered with flour. The amount of methoprene deposited in flour was quantified using an HPLC method which was accurate to 0.5 mg/kg. Sample preparation of less than 1 h was sufficient for 48 samples to quantify methoprene with HPLC.